Lack of Trust and its Influence on the Installation of the COVID-19 Contact-Confirming Application in Japan - Artima Kamplean; Hitoshi Mitomo; Tokio Otsuka (International Telecommunications Society (ITS), 2022)
This study aims to investigate the influence of different types of trust on the installation of the COVID-19 Contact-Confirming Application (COCOA) in Japan with data collected from both installed and non-installed users. Despite the country's digital readiness, Japanese people hesitate to install the application for notifying contact with an infected person and it has not been widely adopted in Japan. Previous literature agrees that trust and privacy concern has been a primary issue for installing the application. The present study adopts the extended valence framework assuming that trust directly influences the user's perception of both negative and positive utility of the contact-confirming application which results in the installation. Novel Coronavirus (Covid-19) was first reported in December 2019 and World Health Organization (WHO) announce the disease as a pandemic in March 2020 (WHO, 2020). Later WHO recommended using a digital tool for controlling infectious diseases as the pandemic surges worldwide. Japan also launch a Contact Confirming Application (or COCOA) developed by the Ministry of Health, Labour and Welfare of Japan in June 2020. Despite high expectations, the application was not widely adopted. This leads to our motivation of what could be a cause of this hesitation in installing COCOA in Japan. After a literature review, we found that number of literature and reports from WHO agree that trust in government and privacy concerns play the key factor in adoption. The literature also mentioned the digital divide as one obstacle in adopting the tracing application. However, it does not seem to be an issue in Japan since the country has a high penetration rate of smartphones and ICT readiness. Because most research focuses on an intention to adopt phase, there is still a lack of empirical evidence from users in the literature regarding a contact tracing application. This study can contribute to the gap in the literature with the data from actual users in Japan. (...)
Keywords: 330; Contact confirming application; COVID-19; Japan; Pandemic; Privacy; Trust in Government; Trust in media